2002
DOI: 10.1007/s00216-002-1330-y
|View full text |Cite
|
Sign up to set email alerts
|

Total synchronous fluorescence scan spectra of petroleum products

Abstract: Extending the two-dimensional synchronous fluorescence scan to a three-dimensional total synchronous fluorescence scan (TSFS) spectral measurement gives the total synchronous fluorescence characteristics of a multifluorophoric sample at various possible wavelength intervals (Deltalambda), which could help to characterize multifluorophoric systems better. TSFS spectra of petroleum products such as diesel, kerosene, petrol, engine oil etc., available in the Indian market, are reported. Fluorescence in these samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…Because of the limited ability as an exact diagnostic tool of conventional fluorescence, advanced and more complex fluorescence techniques such as synchronous excitation [5], fluorescence life time measurement [6], total synchronous fluorescence [7], and low temperature fluorescence [8] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the limited ability as an exact diagnostic tool of conventional fluorescence, advanced and more complex fluorescence techniques such as synchronous excitation [5], fluorescence life time measurement [6], total synchronous fluorescence [7], and low temperature fluorescence [8] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Oil degradation was not classified by individual parameters, but an overall change in the condition over time. Similar studies have shown its use for identifying various different products of petrochemicals with similar composition to synthetic lubricants 53 . Figure 17: PCA of data from samples taken at 5000km and 10,000km 52 In Figure 17, Principal Component Analysis (PCA) of samples is shown.…”
Section: Direction Of Motionmentioning
confidence: 91%
“…Thus, a simple and narrower spectrum is obtained in SFS compared to conventional fluorescence measurements. This technique has been successfully applied to multi-component analysis (7)(8)(9)(10)(11)(12) and petroleum products analysis (13)(14)(15) and also to analyse PAH adducts (16)(17)(18)(19) and for the detection of metabolites of PAHs in human urine (20).…”
Section: Introductionmentioning
confidence: 99%